2017
DOI: 10.1109/tpwrd.2016.2574566
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Modelling of Power-Dependent Harmonic Characteristics of Modern PE Devices in LV Networks

Abstract: This paper presents results of experimental and analytical evaluation of power-dependent harmonic emission of three common types of modern low voltage (LV) power electronic (PE) devices. After a detailed analysis of comprehensive test results, based on both existing and new waveform distortion indices, the development of component-based models of PE devices is discussed. The paper demonstrates the importance of including PE devices' controls for accurate modelling of their characteristics over the entire range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Based on the available scientific works, e.g. models shown in [3][4][5][6][7][8][9][10], it can be concluded that the reduction of model complexity does not lead to poor performance in comparison with the state-of-the-art models used in the literature, as long as the devices in question satisfy the given assumptions of angle distributions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the available scientific works, e.g. models shown in [3][4][5][6][7][8][9][10], it can be concluded that the reduction of model complexity does not lead to poor performance in comparison with the state-of-the-art models used in the literature, as long as the devices in question satisfy the given assumptions of angle distributions.…”
Section: Resultsmentioning
confidence: 99%
“…A rigorous component-based modelling of modern switchedmode power supply, photovoltaic (PV) inverter and electric vehicle charger has been shown in [9]. In this work, authors also introduced an influence of changing power operating mode on resulting harmonic emission levels as well as gave an important remark to test modern PE in presence of non-sinusoidal supply voltage waveform.…”
Section: Introductionmentioning
confidence: 99%
“…Eqs. (7) and (8) present the model in a compact and extended matrix form, respectively. I is the vector of currents, Y is the coupled matrix of admittances, ΔV is the variation of the voltage signals, and is the vector of reference currents [11], whose dimensions are given by H and K, which represent the highest odd harmonic order used for current and voltage signals, respectively.…”
Section: Norton Equivalent Modelmentioning
confidence: 99%
“…Generally, electric loads can be studied using static models based on fundamental frequency, such as ZIP and exponential models, which are mathematical representations that relate the active and reactive powers consumed as a function of the supply voltage root mean square (RMS) value [7]. Multifrequency models such as the Norton equivalent model may also be used, which are predominantly applicable to loads with switched-mode power supplies (SMPSs), such as appliances and lighting loads, and converters, such as battery chargers or photovoltaic inverters [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it becomes essential to understand and predict the PV system characteristic which demands a comprehensive study for assessment of the impacts of PV system connectivity in terms of dynamic behaviour in changing working conditions and disturbances caused in the system (Sangwongwanich and Blaabjerg, 2019). Despite all its cherished advantages, PV systems connectivity also bring into the challenges of affecting the quality of power in terms of harmonic contamination (Yang et al , 2016), unbalancing (Xiao et al , 2017), increased reactive power demand (Ehtesham et al , 2018) and voltage fluctuations (Xu et al , 2017).…”
Section: Introductionmentioning
confidence: 99%